Unpacking the Complexities of Emotional Responses to External Feedback, Internal Feedback Orientation and Emotion Regulation in Higher Education: A Qualitative Exploration - Lan Yang; Yiqi Wu; Yuan Liang; Min Yang (Systems, 2023)
Research suggests that unpleasant emotions induced by feedback may reduce its efficiency in enhancing students’ performance, which is a crucial issue to address in education. In the context of Chinese language instruction in higher education, this study sought to investigate how students regulate their emotions as a result of feedback through the lens of individuals’ feedback orientation. In light of the feedback orientation lens and its conceptual framework, we applied in-depth qualitative interviews to explore how students experienced feedback, the negative emotions they experienced, and the emotion regulation strategies they used. Eleven undergraduates across years one to five joined our in-depth interviews. Students reported negative emotions when they received feedback that did not live up to their expectations or was unrealistic for them to accept. However, students’ feedback orientation supported their emotion regulation techniques, which in turn supported students’ adaptive feedback processing to interpret and take action to use feedback for academic performance improvement. Students also actively sought further teacher feedback or peer support to deal with a wide range of negative emotions. These findings imply the significance of fostering in students a high level of feedback orientation and the necessity of additional empirical investigation into the relationships between feedback orientation and emotional well-being in higher education. By shedding light on how students regulate the emotions that external feedback causes in them, the study adds valuable qualitative findings to the existing literature on positive psychology research in terms of emotions and emotion regulation. It also emphasizes how crucial students’ personal feedback orientation is for improving emotional well-being in the context of feedback.